Bacterial Biodiversity of Industrial Soils from Aydın and Trabzon Province - Bahadır Törün; Rabia Gizem Kalyoncu; Esin Poyrazoğlu Çoban; H. Halil Bıyık (International Journal of Secondary Metabolite)
The aim of this study was to determine bacterial biodiversity of industrial soils from Aydın and Trabzon Province using morphological, cultural, biochemical and molecular methods. Factory wastes, detergents, pesticides and gasoline are accepted as pollutants to the environment. In this study a total of 65 samples which can tolerate xylene, acetone, chloroform and methanol were acquired. According to the Bergey’s Manual of Systematic Bacteriology morphological, cultural and biochemical tests, 48 of these samples were found to be Bacillus sp. and 17 of them were found to be Pseudomonas sp. For molecular identification 16S rDNA-PCR method was used. Seven different genera and a total of sixteen species were found as a result of the study.